Radiographic Morphometric Measurements of the Donkey’s Distal Hind Limb - Schaus, Kyra; Wacker, Juliana; Jandowsky, Anabell; Büttner, Kathrin; Röcken, Michael; Bartmann, Claus Peter; Justus Liebig University Giessen (My University, 2024)
Morphometric measurements of the toe serve as a reference for the objective assessment of the presence of a pathological condition and as a guide for the correct trimming of the hooves. Therefore, the anatomical differences between horses and donkeys oblige an autonomous database with reference values for the donkey. The aim of this study was therefore to provide readings of the distal hind limb on radiographs of donkeys. Radiographs of the distal hind limb in two projections of 41 generally sound donkeys without lameness in walk were taken after previous hoof trimming and preparation according to a standardized radiographic procedure. A total of 16 lengths and 9 angles were measured and statistically analyzed in each hoof. The dorsal hoof wall is on average 70 to 80 mm long and angled at 55°; the coffin bone runs parallel to the hoof wall. The average founder distance is 17 mm, and the mean sole thickness is 14 mm. The heel angle averages 52°, which is slightly flatter than the hoof wall angle. Correlations with weight and height are observed. Concluding, the morphometric measurements confirm the differences between horses’ reported normal anatomy and the presented donkeys. Disorders can be detected by applying the measurements.
Keywords: ddc:630